Kajian Interaksi dan Persepsi Visual pada Game Cut The Rope dan Angry Birds untuk Mengetahui Challenge Based Immersion - Elizabeth Elizabeth; Intan Rizky Mutiaz; Imam Santosa (Wimba : Jurnal Komunikasi Visual, 2013)
Technological progress supports the development of digital game, so that, through people's lifestyle that relies more and more on wireless devices, games become mobile, easy to access, likable and popular. Accordingly, the purpose of this study is to find the relation between games and its players in regards to the communication process and interactive pattern that exist in Cut The Rope and Angry Birds as mobile physics game.This research is an explorative field analysis that uses Creswell case study divided into literature study, case identification, primary data collection and interpretation as the synthesis of the whole. The result of this research is focused on the visual perception and interaction between players and two researched objects.The result shows that visual element, game play, puzzle-like character and sound effect are the most influential aspects of the games since they are considered suitable to the condition and the ability of the casual game players. Besides that, it is known that visual perception is a representation of the function of a common-theme-object with its interpretation that fits the context in a game. Therefore, visual interaction between the players and the researched games are based on four crucial factors: theme, game play, physics movement and simplified presentations of the visual elements. Through the perceptive process, similar kind of games would create a bonding, called challenge based immersion experience, in which this involvement demands the players to understand rules of the games. Such interaction is not influenced by playing time duration and usually does not cause an addiction to the games. Hence, it is clear that the concept of a mobile game has to be understandable through the games' highly comprehensible way, rules, and purpose.This research is mostly focused on the study of the visual aspect of a mobile game, so others still have the chance to do deeply study of the other three crucial aspects of the mobile game: game play, puzzle-like character, and sound effect.